2021
DOI: 10.1002/dta.3172
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive metabolic study of IOX4 in equine urine and plasma using liquid chromatography/electrospray ionization Q Exactive high‐resolution mass spectrometer for the purpose of doping control

Abstract: IOX4 is a hypoxia‐inducible factor prolyl hydroxylase (HIF‐PHD) inhibitor, which was developed for the treatment of anemia by exerting hematopoietic effects. The administration of HIF‐PHD inhibitors such as IOX4 to horses is strictly prohibited by the International Federation of Horseracing Authorities and the Fédération Équestre Internationale. To the best of our knowledge, this is the first comprehensive metabolic study of IOX4 in horse plasma and urine after a nasoesophageal administration of IOX4 (500 mg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…For the purification of IOX4 from crude hair extract, two major problems of matrix effect and absorption were encountered. In the early stage of method development, the liquid–liquid extraction with chloroform used for the analysis of IOX4 in horse plasma and urine previously developed was attempted; 16 however, the extraction efficiency was not sufficient for hair analysis, most likely due to relatively high ionization suppression (around 75%). Mazzarino reported that analytical method for IOX4 in human urine equipped with strong cation exchange (SCX) solid‐phase extraction (SPE) showed high extraction recovery (88%) and acceptable matrix effect (33%) 57 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the purification of IOX4 from crude hair extract, two major problems of matrix effect and absorption were encountered. In the early stage of method development, the liquid–liquid extraction with chloroform used for the analysis of IOX4 in horse plasma and urine previously developed was attempted; 16 however, the extraction efficiency was not sufficient for hair analysis, most likely due to relatively high ionization suppression (around 75%). Mazzarino reported that analytical method for IOX4 in human urine equipped with strong cation exchange (SCX) solid‐phase extraction (SPE) showed high extraction recovery (88%) and acceptable matrix effect (33%) 57 .…”
Section: Resultsmentioning
confidence: 99%
“…All experimental procedures were approved by the Animal Welfare and Ethics Committee of the Laboratory of Racing Chemistry (LRC) (authorization number 20-06) as reported earlier. 16 After a nasoesophageal administration of IOX4 at a dose of 500 mg to three thoroughbred mares (with chestnut or bay hair) for three consecutive days, six bunches of mane hair (approximately 5 mm in diameter and the hair length ranging from approximately 10 to 16 cm) were collected from each horse by cutting at 0 (pre), 1, 2, 3, and 6 month(s) postadministration at different locations of the horse's mane area. The cuts were made as close to the skin as possible.…”
Section: Administration Studymentioning
confidence: 99%
See 3 more Smart Citations